Giant pediatric tubercular retropharyngeal abscess: a rare case - Raheja, Vinny; Kumari, Manisha; Goel, Ashiya; ., Aman (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2020)
A 9-year old child presented with tubercular retropharyngeal abscess leading to stridor. Tubercular retropharyngeal abscess is an extremely rare condition in children. Early management reduces the risk of lethal complications. Due to the absence of classical signs, the diagnosis may be delayed. Therefore, adequate radiological investigations and microbiological studies of aspirate must be done to rule out tubercular aetiology. Conservative medical management should be given in uncomplicated cases. Surgical drainage must be done in cases resistant to medical therapy or presenting with complications.